Organ Donation: opinion and knowledge of college students about brain death - Tessmer, Mateus Germano Scaglioni (2011)
Purpose: identifying prevalence of organ donation intention in a sample among college students defining the main reasons to refuse the organ donation and verifying their understanding and acceptance as to brain death. Methods: A cross-over and randomized study. The sample included 485 freshmen. Independent variables analyzed were sex, age, type of high school, place of residence and socioeconomic level. The students’ opinion on organ donation was analyzed by using direct questions about their organ donation intention, their reasons for not being donors and two similar questions, except by the replacement of the term death to brain death. Result: Of all individuals interviewed, 42.3% had age <20 years. As to organ donation 65.1% answered they had intention to be organ donors after their deaths. However 40.2% of students did not informed having some close relative willing to donate their organs. When asked why people do not donate their organs, “lack of knowledge” was the main reason for people’s unwillingness for the organ donation after death. Most respondents (87.1%) would authorize donation of a relative’s organs after death who had previously declared their willingness to do so. However, only 60.3% would authorize it when the term “brain death” was used as death. Besides, if the interviewed person did not know their relative’s opinion on organ donation, just 34% would authorize donation. Conclusion: When the term brain death was used instead of death, the organ donation intention of students decreased 26% showing that part of them does not understand brain death as death. The understanding about this issue is necessary for the organ transplant can become a feasible therapeutic option.